Повесть о юноше и чародее в славянской книжности - Gritsevskaya, Irina M.; Lytvynenko, Viacheslav V. (Studia Ceranea, 2022)
A Narrative about a Young Man and the Magician Mesites in the Slavonic Medieval Tradition. This article is devoted to the study of the Narrative about the Young Man and Magician that widely circulated in the Medieval Slavonic tradition. The authors analyze the existing versions of the Narrative that formed part of the Svodny Paterik and Prolog, and also establish the closest Greek sources. The study explores various Slavonic and Greek recensions of the Narrative and offers their textual analysis. The Slavonic and Greek versions of the text are placed in the Appendix.